Uma Proposta de Ensino dos Números Inteiros Baseada na Resolução de Problemas - Lara, Cybelle Passos Bezerra (2021)
The observation of students’ mathematical gaps motivated the search for a teaching methodology that would increase learning efficiency. Therefore, this work aims to demonstrate the benefits and feasibility of using the problem solving methodology in the teaching of integer numbers. With this in mind, from the theoretical study of the problem solving methodology, five activities were elaborated with the purpose of helping the elementary school teacher in the use of this methodology. The first activity has the objective of introducing whole numbers as an expansion of natural numbers, working on the idea of the opposite number, showing that zero gains a new referential meaning with the introduction of whole numbers. In it, a technological resource was used to make teaching more attractive. The second, third, fourth and fifth activities have the purpose of working the four operations with whole numbers. For this purpose, two manipulative models were used: the number line with arrows and the two-color model. Aiming at the same purpose, the use of textbooks in the context of teaching whole numbers with and without this methodology was explored. As well as how much the degree in mathematics enables teachers to teach mathematics through these methodologies. As a result, it was observed that the methodology brings a range of advantages to the teaching of mathematics, including: developing confidence and potential in the student regarding their ability to do mathematics, it is more pleasurable for the student and teacher and concentrates the attention of students to ideas and gives meaning to them, thus, the formalization of mathematical concepts and theories made by the teacher starts to make more sense for students. The analysis of textbooks showed that this is a good instrument in the Directed Study teaching technique, however, it needs adaptations to be used in the problem-solving methodology. The textbook has its place in the way of teaching mathematics to solve problems and the approach to teaching through problem solving as a source of problems, but the teacher must make some adaptations. In addition, it is believed that changes that bring pedagogy closer to mathematical content during teacher education will contribute to the improvement of mathematics teaching in the country, since its disassociation leads to a teacher less able to understand the learning process and, therefore, with difficulty in stimulating him. It is also less educated about the use of methodologies, such as problem solving, and models that can be used in teaching. In short, the use of problem solving methodology not only serves the purpose of improving the mathematics proficiency of students in elementary school due to its efficiency, but also makes teaching and learning less painful for teachers and students.